2003
DOI: 10.1016/s0304-4165(03)00118-1
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy of Tobacco Mosaic Virus

Abstract: The dielectric properties of the Tobacco Mosaic Virus (TMV) have been measured using time domain dielectric spectroscopy (TDDS) in the temperature range from 1 to 40 jC. A single dielectric dispersion is observed in the MHz range. The activation energy of the process is found to be in the range 1 -2 kcal/mol. The experimental data could not be completely accounted for by current theoretical models, but evidence indicates that the dielectric loss arises from polarisation of charge on and around the virus. D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Image analysis of 100 virus particles revealed an average size for TMV of 280nm in length and 17nm in width (Fig 2). The ultrastructure in TMV-infected cells and the size of virions observed in this study were found to be in accordance with TMV-induced ultrastructural properties in tobacco and the size range of TMV particles previously reported in the literature [9][10][11][12][13][14][15] . …”
Section: Representative Resultssupporting
confidence: 91%
“…Image analysis of 100 virus particles revealed an average size for TMV of 280nm in length and 17nm in width (Fig 2). The ultrastructure in TMV-infected cells and the size of virions observed in this study were found to be in accordance with TMV-induced ultrastructural properties in tobacco and the size range of TMV particles previously reported in the literature [9][10][11][12][13][14][15] . …”
Section: Representative Resultssupporting
confidence: 91%
“…These studies provide the ability to trap and manipulate nanoparticles with a real-time detection method desirable in molecular analysis, virology, clinical, and environmental fields. Concerning environmental applications, Morgan and coworkers have extensively studied two nonenveloped viruses: cowpea mosaic virus (CPMV) [58] and tobacco mosaic virus (TMV) [59][60][61]. Previously, in the late 1990s, Morgan and Green used mathematical modeling to predict the dielectrophoretic response and crossover frequency of TMV, finding that at frequencies below the crossover TMV exhibited positive DEP, and above the crossover negative DEP [59].…”
Section: Virus Monitoringmentioning
confidence: 99%
“…Assuming that the protein undergoes a reversible two-state transition from native ( ) to unfolded ( ) states, the equilibrium constant can be defined as (1) Here, is the fraction of protein in the native state, is the gas constant, is the temperature (in degrees Kelvin), and is the midpoint temperature (defined as the temperature at which is equal to 0.50 and is equal to 1). The signal ( is any observable, in this case, either the UV/VIS absorbance or the peak frequency) was equal to (2) where and are, respectively, the native and unfolded baselines, defined as linear functions of temperature. An alternative baseline-free approach [28] was also used in which…”
Section: Spectroscopy and Thermal Denaturationmentioning
confidence: 99%
“…The technique has been successfully applied to biological specimens using various methods of application including time-domain reflectometry [2], [3], transmission lines [4], coaxial probes [5], and microfabricated waveguides [6]. While these studies have yielded potentially useful results, many of them suffer from one or more of the following disadvantages.…”
mentioning
confidence: 99%